2017
DOI: 10.1542/peds.2017-0615
|View full text |Cite
|
Sign up to set email alerts
|

US Emergency Department Trends in Imaging for Pediatric Nontraumatic Abdominal Pain

Abstract: CT imaging for pediatric patients with nontraumatic abdominal pain has plateaued since 2007 after the steady increase seen in the preceding 9 years. Among this population, an increased likelihood of CT imaging was demonstrated in general EDs compared with pediatric EDs, in which there was a higher likelihood of ultrasound imaging. Dissemination of pediatric-focused radiology protocols to general EDs may help optimize radiation exposure in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 20 publications
1
20
1
Order By: Relevance
“…Computed tomography scan usage certainly rose into 2007, but the rates are unclear afterwards (Larson et al 2011). Recent studies are piecemeal and often department specifi c, but it appears that usage has leveled off or decreased recently (Niles et al 2017).…”
Section: Some Helpful Advancesmentioning
confidence: 99%
“…Computed tomography scan usage certainly rose into 2007, but the rates are unclear afterwards (Larson et al 2011). Recent studies are piecemeal and often department specifi c, but it appears that usage has leveled off or decreased recently (Niles et al 2017).…”
Section: Some Helpful Advancesmentioning
confidence: 99%
“…Epidemiologic studies have shown that in utero exposure to radiation is associated with higher incidence of pediatric cancers, but data related to rates of pediatric and adult cancers are relatively scarce [60]. In recent years, CT scanning has become the favored imaging modality in many clinical scenarios and is likely to see even further increases in use going forward [61][62][63]. As such, CT utilization in pediatrics has increased markedly over the last 20 years.…”
Section: Patient Exposure To Radiationmentioning
confidence: 99%
“…There are data to suggest an association between hospital type and pediatric mortality for critically ill children, even though this outcome measure is confounded by overall low pediatric mortality rates . The evidence for substantial variability among EDs in the rates of computed tomographic imaging in pediatric trauma and children with abdominal pain is more robust. While the clinical outcomes are comparable between general and pediatric EDs, the rates of unnecessary exposure to ionizing radiation are different and constitute a higher risk to children in the general ED setting.…”
Section: Current State Of Pemmentioning
confidence: 99%